Effect of zirconium chelate on cadmium stressed wheat (Triticum aestivum L. MV.20) seedlings - Fodor, Marietta; Hegedűs, Attila; Stefanovits-Bányai, Éva (Acta Biologica Szegediensis, 2005)
Wheat seedlings were grown hydroponically, for the heavy metal treatment 200 μM Cd acetate was applied. Nutrient solutions were also supplemented with a water-soluble zirconium ascorbate complex (Zr-ASC) at several concentrations. Our results indicated that wheat seedlings have accumulated great amounts of zirconium and cadmium in their roots and shoots. Zirconium uptake was increased under Cd stress; however, its translocation to the leaves was mitigated. Increased activities of guaiacol peroxidase (POD), ascorbic acid peroxidase (APX) and glutathione reductase (GR) reflected a Cd induced oxidative challenge in plant cells. Cadmium induced heavy metal stress symptoms could be alleviated by 10 and 33 μM Zr-ASC, which was also confirmed by the reduced activities of all the tested antioxidant enzymes.